The Idea of Independent Judicial Ethics Courts in Indonesia: Gagasan Pengadilan Etik Kehakiman Independen Di Indonesia - Dina Kartikasari; Saiful Risky (APHTN-HAN, 2025)
This research was conducted to conceptually explore the urgency of the establishment and institutional pattern of the special ethical judicial institution of judicial power. This is driven by the growing global interest in state ethical practices, driven by the ineffectiveness of the law in maintaining public trust. Therefore, fostering and controlling the ideal behavior of judges is considered better through an ethical system, with the law as a last resort. This concept is reinforced by the idea of constitutional ethics, which is equivalent to constitutional law. Normative juridical research methods with legal and conceptual approaches are used in this study. The results of the analysis show that its development leads to the stage of functional ethics, namely the codification and positivization of ethics with the support of institutional infrastructure for its enforcement. The idea of a judicial ethics court strongly supports the strengthening of ethical institutions to build integrity in judges' behavior. The institutional construction of the ethics court must be in accordance with judicial principles in general and structurally the same as the Supreme Court and the Constitutional Court. However, it is possible that establishing an ethics court also has challenges that must also be considered.